2018
DOI: 10.1007/s10333-018-0634-2
|View full text |Cite
|
Sign up to set email alerts
|

Doing what with whom? Stakeholder analysis in a large transdisciplinary research project in South-East Asia

Abstract: The transdisciplinary research project LEGATO analysed the combined generation of provisioning, regulating and cultural ecosystem services in wet rice agriculture in South-East Asia and applied ecological engineering to future-proof it against global change and environmental pollution challenges. Due to its transdisciplinary character and the sheer size, a systematic stakeholder involvement was inevitable. Starting with stakeholder identification by snowballing from a limited number of contacts, we derived a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…2015; Schmidt and Pröpper 2017; Spangenberg et al. 2018). The steering committee took this finding seriously: successful stakeholder collaboration requires clearly defined objectives and goals (Reed 2008; Wesselink et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2015; Schmidt and Pröpper 2017; Spangenberg et al. 2018). The steering committee took this finding seriously: successful stakeholder collaboration requires clearly defined objectives and goals (Reed 2008; Wesselink et al.…”
Section: Methodsmentioning
confidence: 99%
“…This model was grounded in the principle that those who conduct river governance in the state should formulate it to better employ it (Pohl and Hirsch 2007;Lang et al 2012). However, it has been shown that by not articulating desired objectives, a highly collaborative project risks pursuing diverging intentions and expectations, and this may limit the impact of the participatory research and may result in disappointment among those involved (Wesselink et al 2011;Spangenberg et al 2015;Schmidt and Pr€ opper 2017;Spangenberg et al 2018). The steering committee took this finding seriously: successful stakeholder collaboration requires clearly defined objectives and goals (Reed 2008;Wesselink et al 2011), and relied on facilitation to balance the need for well-defined goals with inclusivity and avoid divergence in intentions and expectations among participants.…”
Section: Methodsmentioning
confidence: 99%
“…These stakeholders include farmers, association of farmers, consumers, government or authorities, raw material suppliers, industry associations, competitors, general public, research institution, and middlemen (Flor et. al., 2019;Spangenberg et. al., 2018;Indumathi et.…”
Section: Stakeholders' Participatory Approach In Rice Agribusinessmentioning
confidence: 99%
“…Previous research has identified the need for stakeholder analysis to increase the development of the rice agricultural sector. Stakeholder analysis research of agriculture projects in South-East Asia found that farmers, their extension workers, and local authorities are the influential factors (Spangenberg et. al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus land use planning is crucialtransforming agricultural land into industrial zones or selling it to foreign investors who, in the extreme, may concert it to golf courses [5], endangers food security in the medium to longer term. Such land conversion has caused dissatisfaction and hidden conflicts between farmers and planning authorities which despite not breaking into the open due to uneven power potentials, undermine social cohesion and trust [21].…”
Section: From An Agricultural To An Industrial Economymentioning
confidence: 99%